Feminist Collections, v.24, no.2 (winter 2003) - (:unkn) unknown (My University, 2003)
Subtitle: A Quarterly of Women's Studies Resources.
FROM THE EDITORS. IN MEMORIAM: Esther Lanigan, by Sue Searing. INTRODUCING THE WOMEN & RELIGION REVIEW SERIES: By Lori Rowlett. BOOK REVIEWS: Resources for Teaching “Women & Religion”: Five Readers, by Charlene P.E. Burns. Interpreting Eve: Gender Politics & the Representation of Christian Scripture in the Evolution of Western Culture, by Deborah Louis. The Pedagogical Mystique: Feminist Academic Discourse, by Carmen Faymonville. VIDEO UPDATES & SHORT TAKES: By JoAnne Lehman. Like Catching Waves Upon the Sand: The Challenges of Designing for the Web, by Pamela O'Donnell. E-RESOURCES ON WOMEN & GENDER: By JoAnne Lehman. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Phyllis Holman Weisbard. ZINE AND HEARD (AGAIN): By M.L. Fraser. FEMINIST PUBLISHING/ARCHIVES: By JoAnne Lehman. PERIODICAL NOTES: By JoAnne Lehman. ITEMS OF NOTE: By Mary Photenhauer. BOOKS & AV RECENTLY RECEIVED. SUBSCRIPTION FORM.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Women & Religion Reviews; Zines; E-Sources